Variation in Population Characteristics in Siraha District - Yadav, Keshav Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
Nepal’s populat ion has experienced a steady growth for the past several decades. The growing population, at alarming state in Siraha (Nepal), is an indicator of the change in populat ion status. The populat ion of iraha district is slow growing than the country. To sketch the picture of Siraha population status, indicators obtained from census like size, growth rate, density, dist ribution, composit ion, dependency ratio, age at marriage, Absentees, literacy status, religion, caste/ethnicity as well as the major mother tongue. Academic Voices Vol.6 2016: 5-10